35. Jahrestagung Der Deutschen Arbeitsgemeinschaft Zum Studium Der Leber 2019
DOI: 10.1055/s-0038-1677228
|View full text |Cite
|
Sign up to set email alerts
|

The ATG16L1 Gene Variant rs2241880 (p.T300A) Is Associated With Susceptibility to HCC In Patients with Cirrhosis

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…Moreover, our findings proved that GG genotype carriers are 3.2 times riskier to progress to cirrhosis than those carrying the AA genotype while AG genotype carriers are 6.4 times more prone to this risk and that those harboring the G allele are 2 times more prone to progression to liver cirrhosis than individuals with C allele. This is concordant with [ 47 ] study which reported that the ATG16L1 G allele was more prevalent in HCC patients when compared to controls (P = 0.022). G allele carriers were 1.76 folds at more risk to develop HCC (ORs = 1.76, 95% CI: 1.07–2.88).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, our findings proved that GG genotype carriers are 3.2 times riskier to progress to cirrhosis than those carrying the AA genotype while AG genotype carriers are 6.4 times more prone to this risk and that those harboring the G allele are 2 times more prone to progression to liver cirrhosis than individuals with C allele. This is concordant with [ 47 ] study which reported that the ATG16L1 G allele was more prevalent in HCC patients when compared to controls (P = 0.022). G allele carriers were 1.76 folds at more risk to develop HCC (ORs = 1.76, 95% CI: 1.07–2.88).…”
Section: Discussionsupporting
confidence: 92%